FRESHWATER SCARCITY AND IRRIGATION CHALLENGES IN CENTRAL ASIA: A GROWING THREAT TO DROUGHT PREVENTION (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Central Asia, a region renowned for its vast deserts and ancient civilizations, is grappling with a pressing issue: freshwater scarcity. This scarcity, exacerbated by climate change, unsustainable irrigation practices, and population growth, poses a significant threat to agriculture, ecosystems, and human well-being. This article delves into the complexities of freshwater management in Central Asia, the challenges faced by irrigation systems, and the crucial steps necessary to mitigate drought risks.